Clays as Vehicles for Drug Photostability - Monsuêto C. da Rocha; Thais Galdino; Pollyana Trigueiro; Luzia M. C. Honorio; Raquel de Melo Barbosa; Santiago M. Carrasco; Edson C. Silva-Filho; Josy A. Osajima; César Viseras (Pharmaceutics, 2022)
Clay minerals are often used due to their high adsorption capacity, which has sparked interest in their biological applications to stabilize drugs and pharmaceutical products. This research aims to summarize information about the stability of drugs, cosmetics, dermocosmetics, and pharmaceutical compounds incorporated in the structure of different clay minerals. The databases used to search the articles were Web of Science, Scopus, PubMed, and Science Direct. Photostabilization of these compounds is reviewed and its importance demonstrated. For biological applications, the increase in solubility and bioavailability of clay minerals has proven useful for them as drug carriers. While their natural abundance, low toxicity, and accessible cost have contributed to classical applications of clay minerals, a wide range of interesting new applications may be facilitated, mainly through incorporating different organic molecules. The search for new functional materials is promising to challenge research on clay minerals in biological or biotechnological approaches.